Bridging policy and practice for inclusive climate adaptation in the Philippines: Insights from Quezon and Batangas - Gartaula, Hom Nath; Hellin, Jon; Eschavez, Chona; Raviz, Jeny; Bacud, Susan; Laborte, Alice; Rosimo, Magnolia; Datoon, Rodmyr; Gonsalves, Julian (International Rice Research Institute, 2025)
The Philippine agricultural sector illustrates how climate change exacerbates vulnerability and inequality. Incremental adaptation, while important, is insufficient. What is needed is transformative adaptation—one that foregrounds equity, justice, and local agency. By positioning marginalized communities, including women, youth, and ethnic minorities, not as passive recipients but as co-creators, the Participatory Action Learning Strategy (PALS) offers an innovation that is iterative, inclusive, and empowering. It bridges the gap between policy frameworks and lived realities, ensuring that resilience is both climate-smart and socially just. In a world where climate change disproportionately affects the most vulnerable, PALS reminds us that resilience is not just about protecting livelihoods—it is about reshaping systems to be fairer, more inclusive, and more democratic.